A review of direct polymerase chain reaction of DNA and RNA for forensic purposes. Issue 4 (31st March 2019) - Lynch, Courtney; Fleming, Rachel
Abstract : Short tandem repeat (STR) profiling is frequently carried out on biological stains in forensic casework, and the application of messenger RNA (mRNA) body fluid identification is becoming more prevalent. Increasing constraints on analysis time, resources, an increase in the number of samples for analysis, and a large backlog of cases creates significant demand for quicker methods that direct polymerase chain reaction (PCR) can help overcome. Direct PCR bypasses DNA and/or RNA extraction, and in some cases, quantification by adding the sample or substrate punch to the amplification reaction. This method is currently used in some laboratories on reference samples. Direct PCR is also a component of portable devices, which could improve efficiency even further by producing results at the scene, and enabling triaging of samples for further testing. Portable devices are currently used for STR profiling of reference samples but not for mRNA profiling. Various concerns regarding the reliability of the method and equipment (portable devices) must first be addressed before incorporation into forensic casework. This review discusses the limitations and factors that need to be considered for direct PCR to be used for the analysis of casework samples, including being used for mRNA body fluid identification. This article is categorized under: Forensic Biology > Forensic DNA Technologies Forensic Biology > Body Fluid Identification Forensic Biology > Applications of RNA Abstract : With advances in technology, direct PCR of DNA and RNA for forensic purposes is now a reality. While early progress has been made, there are still a number of factors that need to be considered. This review describes where direct PCR technology is at and what still requires attention before this technique can become a standard technique in forensic science.